(untitled) (Academicia Globe: Inderscience Research, 2023)
Data of the researches devoted to prevalence of illnesses of genitourinary sphere, concerns only separate nosological units or, as a last resort, their groups. Researches of prevalence of urolithiasis, benign prostatic hyperplasia (BPH), urinary tract infections (UTI), carried out at various times in many countries, in some extent and scale [Apolikhin O. I et al., 2010, Kozhabekov B. S. 1998, Miller D.C., et al., 2009] relate to them. Coverage of the data on the prevalence of diseases estimated on appealability of patients for the medical aid, can be much wider, therefore objectivity of such data is relative, as appealability, in itself, depends on many factors (availability of medical aid, its quality, sanitary culture of the population, its mentality, etc.) And to present an integrated picture of true prevalence of diseases of organs of urinary ways and man’s sexual sphere, not always is obviously possible.